Education on Preventing Sexual Harassment and Violence on Social Media: A Healthy Relationships Movement for Students at SMP Negeri 7 Muaro Jambi - Muhammad Alridho Lubis; Fitriana; Ninil Elfira; Dinny Rahmayanti; Sundari Utami; Muhammad Ichsan; Nur Qomariah Panjaitan (MARAWA: Jurnal Masyarakat Religius dan Berwawasan, 2025)
The use of social media without adequate digital literacy understanding also increases the risk of online sexual harassment and violence. Therefore, comprehensive and sustainable educational interventions are needed to raise students' awareness of the forms of sexual harassment and violence. This community service is crucial to encourage prevention efforts through an educational approach that is youth-friendly, contextual, and participatory, so that students are not only able to recognize forms of violence, but also able to protect themselves, build healthy relationships, and become agents of change in their environment. The objectives of this Community Service are: (a) Increasing students' understanding of forms of sexual harassment and violence on social media, both explicit and covert; (b) Building students' critical awareness of the importance of maintaining boundaries and ethics in interacting in digital spaces; (c) Educating students about the concept of healthy relationships, which are based on respect, equality, and healthy communication; (d) Encouraging students' active participation in sexual violence prevention campaigns, especially on social media, through creative approaches based on their experiences; and (e) Cultivating a safe, inclusive, and violence-free school culture, through collaboration between schools, parents, and the community.